2014
DOI: 10.1073/pnas.1413282112
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of ADAMTS13 by von Willebrand factor

Abstract: The metalloprotease ADAMTS13 cleaves von Willebrand factor (VWF) within endovascular platelet aggregates, and ADAMTS13 deficiency causes fatal microvascular thrombosis. The proximal metalloprotease (M), disintegrin-like (D), thrombospondin-1 (T), Cys-rich (C), and spacer (S) domains of ADAMTS13 recognize a cryptic site in VWF that is exposed by tensile force. Another seven T and two complement C1r/C1s, sea urchin epidermal growth factor, and bone morphogenetic protein (CUB) domains of uncertain function are C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
179
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(200 citation statements)
references
References 58 publications
14
179
0
2
Order By: Relevance
“…Whether the C-terminal domains also interfere with binding of the Cys-rich domain to VWF is unknown. 33,34 In summary, our results demonstrate an important role for the Cys-rich domain in VWF proteolysis and identify hydrophobic residues in both ADAMTS13 and VWF that are critical for efficient proteolysis. These findings are in agreement with previous findings that suggested the presence of extensive contacts between exosites in ADAMTS13 and VWF, involving multiple domains.…”
mentioning
confidence: 61%
“…Whether the C-terminal domains also interfere with binding of the Cys-rich domain to VWF is unknown. 33,34 In summary, our results demonstrate an important role for the Cys-rich domain in VWF proteolysis and identify hydrophobic residues in both ADAMTS13 and VWF that are critical for efficient proteolysis. These findings are in agreement with previous findings that suggested the presence of extensive contacts between exosites in ADAMTS13 and VWF, involving multiple domains.…”
mentioning
confidence: 61%
“…Binding of kringles to fibrin clots and cell surface receptors is assumed to induce a transition to an open form that can be cleaved and converted to plasmin by physiological activators. The metalloprotease ADAMTS13 has its distal domains closed on the catalytic site, and the autoinhibition is removed upon binding of its physiological substrate von Willebrand factor (43).…”
Section: Discussionmentioning
confidence: 99%
“…The first of these properties has, until recently, been explained by the dependence of ADAMTS‐13 proteolytic function on VWF conformation and the exposure of its complementary binding sites. However, it has recently been shown that ADAMTS‐13 undergoes its own conformational change in order to attain a fully active state 22, 23. In this new model of ADAMTS‐13 function the enzyme circulates in a ‘closed’ conformation mediated by binding between its spacer and CUB domains 22.…”
Section: Introductionmentioning
confidence: 99%